Comparative Blood Profile Of Progesterone, Metabolites And Minerals In Anoestrus, Suboestrus, Repeat Breeding And Normal Cyclic Buffaloes - Butani, M.G.; Dhami, A.J.; Kumar , Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
A comparative study on serum profile of progesterone (P4) and metabolites of 37 anoestrus, 10 suboestrus, 53 repeat breeding and 12 normal cyclic buffaloes revealed that the serum P4 was significantly (P
Keywords: Blood profile; Buffalo; Anoestrus; Suboestrus; Repeat Breeders; Normal cyclic